STUDENT LEARNING MOTIVATION TO SUBJECT TO MAKE APATTERNIN SMK NEGRI 1 GUMANTI VALLEY - Susanti, Rina; Adriani, Adriani; Novrita, Sri Zulfia (Faculty of Tourism and Hospitality - Universitas Negeri Padang, 2016)
This study aims to describe the students' motivation on the subjects to make a pattern in SMK Negeri 1 Gumanti valley, with indicators of alertness, concentration and perseverance. This type of research is descriptive with quantitative approach. The population in this study were all students of class XI 2015/2016 school year who are taking courses to make patterns with the number of 18 students, a sample of this research is all class XI student of SMK Negeri 1 fashion Gumanti valley academic year 2015/2016 with the number 18 students, with the technique of sampling done by total sampling. Data were obtained through a questionnaire that measured with Likert scale. Data were analyzed quantitatively and TCR percentage, in order to obtain the interpretation of the students' motivation on the subjects to make a pattern in SMK Negeri 1 Gumanti valley.Based on the results obtained the following conclusions. Motivation to learn the indicators alertness category is quite high (73.9%). That is still lacking, especially in the case late in the assignment given by the teacher. Motivation to learn the indicators categorized concentration is high (72.1%). That is still lacking, especially in terms of not listening and paying attention to the teacher's explanations seriously. Motivation to learn the persistence indicator category is quite high (71.0%). That is still lacking, especially in terms of understanding the material to make a pattern. Overall the students' motivation on the subjects to make a pattern in SMK N 1 Gumanti valley located in the category is quite high (72.0%). This means that students' motivation on the subjects create patterns need to be improved to make it better. Â Â Kata Kunci: Motivasi Belajar, Membuat Pola